2022
DOI: 10.1002/bse.3128
|View full text |Cite
|
Sign up to set email alerts
|

The versatile role of sustainable market entrepreneurs in market transformation: An intervention framework for institutional change

Abstract: This article investigates in which way sustainable entrepreneurship can generate institutional change that transforms markets towards sustainability. A transformation of models of economic organization and market structures through sustainable entrepreneurship fosters the path towards sustainability. Institutional change involves sustainable market entrepreneurs as institutional entrepreneurs that operate in an effectual manner in different market transformation phases. Sustainable market entrepreneurs while s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 131 publications
0
5
0
Order By: Relevance
“…The literature on the purpose and impact of corporations has shown that an excessive focus on profits can have unintended consequences for the environment, society and corporations themselves (for an interesting overview about sustainable entrepreneurship and business see Argyrou et al, 2021; Knoppen & Knight, 2022; Muñoz & Cohen, 2018). BCs are required to have a double purpose—profits and public common benefit—and as such represent a corporate form that fully integrates sustainability (Hiller, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The literature on the purpose and impact of corporations has shown that an excessive focus on profits can have unintended consequences for the environment, society and corporations themselves (for an interesting overview about sustainable entrepreneurship and business see Argyrou et al, 2021; Knoppen & Knight, 2022; Muñoz & Cohen, 2018). BCs are required to have a double purpose—profits and public common benefit—and as such represent a corporate form that fully integrates sustainability (Hiller, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, certain regions provide significant motivation for enterprises to uphold social responsibility in travel by recognizing high‐quality companies. This compels digital transformation enterprises to consider the feasibility of creating multiple values (Argyrou et al, 2023). A company's establishment of a four‐level safety management system and the convenience model of “business + service” was awarded as a typical project of “Demonstration Project of Standardized Community Business Center”.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the examined companies with a stewardship strategic orientation, the top management triggers a change toward a focus on ecological matters throughout the organization. Ecological concerns (Strauss et al, 2017) are embedded in the business in a way that goes beyond merely identifying and/or discovering business opportunities by also using entrepreneurial skills, knowledge, and networking to generate opportunities in uncertain and transforming environments (Argyrou et al, 2022; Hall et al, 2010; Hummels & Argyrou, 2021; Johnson & Hörisch, 2021). In this way, opportunities are sensed and seized while achieving a sustainability impact based on intuition, knowledge, and networking to support sector‐wide transitions in uncertain ecological and business environments.…”
Section: Discussionmentioning
confidence: 99%